2009
DOI: 10.1214/ejp.v14-614
|View full text |Cite
|
Sign up to set email alerts
|

Intermittence and nonlinear parabolic stochastic partial differential equations

Abstract: We consider nonlinear parabolic SPDEs of the form ∂tu = Lu+σ(u)ẇ, whereẇ denotes space-time white noise, σ : R → R is [globally] Lipschitz continuous, and L is the L 2 -generator of a Lévy process. We present precise criteria for existence as well as uniqueness of solutions. More significantly, we prove that these solutions grow in time with at most a precise exponential rate. We establish also that when σ is globally Lipschitz and asymptotically sublinear, the solution to the nonlinear heat equation is "weakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
231
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 119 publications
(241 citation statements)
references
References 36 publications
10
231
0
Order By: Relevance
“…Throughout, we write 9) as substitute for the approximate spatial gradient of any real function f . We also adopt the following notation…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout, we write 9) as substitute for the approximate spatial gradient of any real function f . We also adopt the following notation…”
Section: )mentioning
confidence: 99%
“…This bound follows essentially from the Appendix of [9]; see also [7]. Therefore, we will not describe a proof.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Foondun and Khoshnevisan [17] have shown that: provided that: (a) inf x |σ(x)/x| > 0; and (b) inf x u 0 (x) > 0. 2 Together these results show that if u 0 is bounded away from 0 and σ is sublinear, then the solution to (1.1) is "weakly intermittent" [that is, highly peaked for large t].…”
Section: Introductionmentioning
confidence: 99%